2021
DOI: 10.3390/cancers13184720
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cancer-Associated Fibroblasts in Cancer Invasion and Metastasis

Abstract: Cancer-associated fibroblasts (CAFs) play a key role in cancer progression by contributing to extracellular matrix (ECM) deposition and remodeling, extensive crosstalk with cancer cells, epithelial-to-mesenchymal transition (EMT), invasion, metastasis, and therapy resistance. As metastasis is a main reason for cancer-related deaths, it is crucial to understand the role of CAFs in this process. Colorectal cancer (CRC) is a heterogeneous disease and lethality is especially common in a subtype of CRC with high st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 147 publications
(182 reference statements)
4
104
0
Order By: Relevance
“…The degradation of the ECM is considered an important marker of the progress of metastasis [13,14,[44][45][46]. Numerous previous studies have revealed that this process is catalyzed by proteins secreted by cancer cells and allows cancer cells to migrate to other tissues or organs [17].…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of the ECM is considered an important marker of the progress of metastasis [13,14,[44][45][46]. Numerous previous studies have revealed that this process is catalyzed by proteins secreted by cancer cells and allows cancer cells to migrate to other tissues or organs [17].…”
Section: Discussionmentioning
confidence: 99%
“…As shown above, CAFs contribute a variety of growth factors to the TME, mediated in part by integrins, and facilitated by cadherins. CAFs are the proposed initiators of EMT in bladder cancer ( Goulet et al, 2019 ) and colorectal cancer ( Asif et al, 2021 ), and this extends to many other cancers, as well ( Fiori et al, 2019 ; Mezawa and Orimo, 2021 ). Taken together, this data suggests a fundamental role for CAFs in the epithelial-mesenchymal cooperation we propose.…”
Section: Cell-cell (E-cadherin Cdh1) and Cell-ecm (α6 Integrin Cd49f)...mentioning
confidence: 94%
“…PDPN makes a complex with MMP14 and co-localizes at cell-surface protrusions, suggesting the potential of ECM destruction at sites [107]. In tumor cell invasion, not only tumor cells but also stromal cells express and secrete MMPs, which contributes to the destruction of the ECM for tumor invasion [108] (Figure 2). Furthermore, PDPN can stimulate TGF-β secretion in oral SCC cells, which activates surrounding fibroblasts, upregulating MMP2 and MMP14 expression [109].…”
Section: Cafmentioning
confidence: 99%